2020
DOI: 10.1080/01942638.2020.1736234
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Participation Meaningful? Using Photo-Elicitation to Interview Children with Disabilities

Abstract: This study was part of the LOOK project (2014)(2015)(2016)(2017), which aimed to develop new rehabilitation practices to strengthen children's participation and agency. The project was managed by Metropolia University of Applied Sciences in collaboration with the Central Union for Child Welfare and was funded by the Social Insurance Institution of Finland (Kela). We extend our thanks to the LOOK project participants, and the children and families who took part in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…From the child's perspective, factors such as suitable assistive devices and adaptations to activity demands, have been identified as relevant factors for meaningful participation in a previous study by Vänskä et al, (2020) [10]. Additionally, positive peer-relationships are important for the children [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the child's perspective, factors such as suitable assistive devices and adaptations to activity demands, have been identified as relevant factors for meaningful participation in a previous study by Vänskä et al, (2020) [10]. Additionally, positive peer-relationships are important for the children [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a study by Maciver et al, (2019), the importance of the adults' attitudes towards creating opportunities for the child's participation were underlined, as well as the need for an individualized approach and flexibility in the routines and structures within the school environment [13]. From the child's perspective, factors such as suitable assistive devices and adaptations to activity demands, have been identified as relevant factors for meaningful participation in a previous study by Vänskä et al, (2020) [10]. Additionally, positive peer-relationships are important for the children [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children who attached higher value to their everyday activities and perceived a higher sense of autonomy needed less assistance, enjoyed their everyday activities more, and their parents reported a higher level of satisfaction with their children’s participation. Previous literature revealed that children with NDD attach value to activities that provide them with an experience of success, fun, belonging, and freedom (Vänskä et al, 2020; Willis et al, 2017). Regrettably, they often experience a low level of autonomy (Lamash & Josman, 2020; Wennberg et al, 2019) as their daily life is highly structured by their parents.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CMAP Book support family and professionals to create a joint understanding in multidisciplinary rehabilitation planning and goal setting resulting in a coherent and common rehabilitation plan with meaningful goals. Use of the photos [33], videos, writing and recordings helps the child's own expression and concretises their views enabling her/his participation in rehabilitation planning, identification of goals and discussion with adults.…”
Section: Discussionmentioning
confidence: 99%